Volatility Spillover between Stock Returns and Oil Prices during the Covid-19 Pandemic in ASEAN - Alexandri, Mohammad Benny; Supriyanto, Supriyanto (International Journal of Energy Economics and Policy, 2022)
This study points to increase global monetary integration as a result of rising volatility spillovers. As a result, analyzing volatility spillovers for international areas that expand and improve through the usage of inventory returns and oil prices is critical. The EGARCH model is used to explore the Volatility Spillovers of oil agencies in five ASEAN international areas during the Covid-19 Pandemic. To assess the interrelationships of the ASEAN stock index as well as the path of volatility, data were acquired from five global sites with very large volatility spillovers, namely Indonesia, Malaysia, Singapore, Thailand, and Vietnam. The findings show that this search is critical for ASEAN traders as well as Filipinos. Furthermore, because accurate forecasting of volatility spillover in global equity markets is required to reduce portfolio risk, this search has a substantial and viable significance.